All-Inorganic Perovskite Solar Cells With Both High Open-Circuit Voltage and Stability - Zhang, Lei; Hu, Tianle; Li, Jinglei; Zhang, Lin; Li, Hongtao; Lu, Zhilun; Wang, Ge (Frontiers in Materials, 2020)
Metal halide perovskite solar cells based on all-inorganic CsPbBr3 have attracted considerable attentions recently, due to their high open-circuit voltage and good stability. However, the fabrication of CsPbBr3 film is limited by the poor solubility of cesium precursors in organic solvents by the one-step method. Here, we successfully fabricated CsPbBr3 film solar cells by employing colloid nanocrystal. The effects of technique parameters, including purification times, anneal temperatures, and spin-coating times on film morphology, optical spectra, and device performance are investigated in detail. The highest power conversion efficiency of 4.57% has been achieved based on a large open-circuit voltage of 1.45 V and a large short-circuit current of 9.41 mA cm−2. A large open-circuit voltage results from the reduced non-radiative energy loss channels and defect states while a large short-circuit current is related to the high conductivity induced by the removal of organic ligands with the increased nanocrystal electronic coupling. Furthermore, excellent stability in air is disclosed on the unencapsulated device suggesting the enormous potential for developing high open-circuit photovoltaic devices with high stability in future.